Immunohistochemical localization of Kisspeptin and its receptor in the placentome of buffalo (Bubalus bubalis) - MISHRA, G K; PATRA, M K; KARIKALAN, M; SINGH, S K; KUMAR, H; KRISHNASWAMY, N (The Indian Journal of Animal Sciences, 2022)
Evidence for extra-hypothalamic expression of kisspeptinergic system is emerging. The present study documents the imuunolocalization of the kisspeptin and its receptor in the placentome of buffalo. Gravid uterus was collected from the abattoir and gestational age was estimated by crown-rump length of the fetus. A section of placentome containing the caruncle and cotyledon was used for immunohistochemistry. The expression of Kp and its receptor was evident in the feto-maternal junctions with prominent localization in the mononucleate and binucleate cells. In conclusion, the present study supports possible role of placental kisspeptin during pregnancy in the ruminants